2021
DOI: 10.1111/cns.13645
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐1 ameliorates perioperative neurocognitive disorders in aged mice

Abstract: Introduction The incidence of perioperative neurocognitive disorders (PND) is higher in the elderly patients undergoing surgery. Microglia activation‐mediated neuroinflammation is one of the hallmarks of PND. Galectin‐1 has been identified as a pivotal modulator in the central nervous system (CNS), while the role of galectin‐1 in PND induced by microglia‐mediated neuroinflammation is still undetermined. Methods An exploratory laparotomy model anesthetized with isoflurane was employed to investigate the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“… 5 , 6 Surgery activates an immune response and results in the release of systemic proinflammatory factors and eventually leads to neuroinflammation. 7 , 8 , 9 Studies have shown that microglia are activated by peripheral proinflammatory cytokines 10 and can release additional proinflammatory cytokines, exacerbating neuroinflammation and brain damage. 11 Once activated by proinflammatory cytokines in the brain, microglia tend to separate into two “polarizing” phenotypes M1 and M2, sometimes associated with the release of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Surgery activates an immune response and results in the release of systemic proinflammatory factors and eventually leads to neuroinflammation. 7 , 8 , 9 Studies have shown that microglia are activated by peripheral proinflammatory cytokines 10 and can release additional proinflammatory cytokines, exacerbating neuroinflammation and brain damage. 11 Once activated by proinflammatory cytokines in the brain, microglia tend to separate into two “polarizing” phenotypes M1 and M2, sometimes associated with the release of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Pathway enrichment showed that EC1 was highly expressed in inflammation-related pathways, such as GO-POSITIVE-REGULATION-OF-TNF-MEDIATED-SIGNALING-PATHWAY and GO-REGULATION-OF-MONOCYTE-CHEMOTAXIS ( Supplementary Figure S3 C). At the transcriptional level, EC1 was also found to highly expressed inflammatory TFs such as Jun and Fos [ 21 , 22 ] ( Supplementary Figure S3 D). The diverse functional involvement of ECs prompted us to explore cell–cell communications of EC1, the crosstalk showed that EC1 could interact with other cells through many chemokines and receptors ( Supplementary Figure S3 E).…”
Section: Resultsmentioning
confidence: 99%
“…PND are common neurological complications that include postoperative delirium (POD), postoperative cognitive decline (POCD), and delayed neurocognitive recovery and occur in 10% to 54% of patients after surgery. 2 Although advanced age, neuroinflammation, and cerebrovascular dysfunction are thought to be important factors for cognitive impairment in the pathogenesis of neurodegenerative disorders, [38][39][40][41] the exact mechanisms underlying the pathogenesis of PND remain largely unclear. Recently, several clinical studies have indicated that diabetes and acute perioperative hyperglycemia are independent risk factors in the development of PND.…”
Section: Discussionmentioning
confidence: 99%